Pengaruh Kompetensi Dan Leader Member Exchange Terhadap Kinerja Penyidik Dengan Anti Perubahan Sebagai Moderasi Pada Ditreskrimum Polda Jateng - Kurniasih, Dwi; Indarto, Indarto; Santoso, Djoko; Savitri, Fania (Jurnal Litbang Polri, 2024)
In crime investigation, which is an indicator of an investigator's performance, technology can assist the National Police in collecting electronic evidence, performing digital forensic analysis and using the latest search techniques. Improving investigative capabilities is important for tracking criminals, gathering strong evidence and investigating crimes more effectively. This research serves to analyse the relationship between competence and leader member exchange on investigator performance with anti perubahan as a moderating variable in the performance of Regional Police Criminal Investigation Investigators. Central Java. This research uses quantitative methods using questionnaires to collect the necessary data. The sample in this study consisted of 68 Regional Police Investigators in Central Java obtained through a simple random sampling method. The analysis used to process the data is moderated regression analysis using SPSS 25. The results of this research show that competency and leader member exchange have a positive and significant effect on investigator performance, and anti perubahan successfully moderates the influence of leader member exchange on investigator performance.